Information Exchange Problems Between 3D Modelling and Process Planning Modules - Jyri Papstel; Alo Saks; Indrek Kiolein (Communications - Scientific letters of the University of Zilina, 2000)
The objective of this project is to develop atool for communication between 3DCAD and process planning. Our accomplishments so far have been: (i) Transfer of the CAD data model and other product information from the 3D CAD system (Solid Edge) to a database module, (ii) the part/detail and feature classification module. The approach is based on STEP technology to define computer-aided tools for data structuring and management of product knowledge implemented on the relational database. Problems of part and form feature description play a crucial role in this framework. In 3D modelling Form Feature (FF) based design activities are the most effective approach. A number of FF definitions have been introduced for different implementations (design features, manufacturing features, tool features etc). However, the consensus in the field has not been reached and often the terms used are not clear for the users. In the present paper a short introduction is given to solve the afore described problems.